Long-term copper exposure induced pyroptosis and inflammation of rat spleen through intestinal-splenic axis - Jinwen Quan; Xiaoyue Chang; Siying Liu; Ting He; Gaolong Zhong; Zhonghua Liu; Wenlan Yu (Ecotoxicology and Environmental Safety)
Copper is an essential micro-element in animal growth. Tribasic copper chloride (TBCC), as an important source of animal feed copper, is widely used in agricultural production. Multiple studies have shown that excessive intake of copper can affect the immune function of animals and lead to disease or death. The intestine-spleen axis, which is the interaction between the spleen, intestines and gut microbiota, is closely linked to immune function in the body. However, the mechanism of intestine-spleen axis affecting TBCC induced immune dysfunction in rats has not been revealed. In this study, we analyzed the impacts of different doses of TBCC on the intestine, gut microbiota and spleen of rats, and investigated their relationship in the process. Our results demonstrated that under copper exposure, the structural integrity of the intestinal epithelium was compromised, resulting in a significant downregulation of genes and proteins expression levels related to the intestinal barrier (Zonula occludens-1, Claudin-1 and Occludin). Additionally, copper perturbed the composition of the rat intestinal microbiota, altered the abundance and diversity of the microbial community. Copper entered the spleen via the intestine-spleen axis, leading to structural damage in the spleen and activation of the NFκB signaling pathway, and increased pro-inflammatory cytokines (IFN-γ, TNF-α, IL-18, and IL-1β), ultimately causing pyroptosis and inflammation in the spleen. These findings offer a novel perspective on how copper may induce spleen injury through the intestine-spleen axis.